Thermal insulation for refrigeration pipe made of polyurethane reinforced coconut husk and rice husk - Khalid, A. M.; Zuhri, M. Y. M.; Hairuddin, A. A.; As’arry, A. (Springer Nature Singapore, 2023)
The abstract should summarize It is well-known that the conductivity coefficient (K-value) of insulator is an important factor for the heat transfer process. Consequently, objective of this research is to investigate the capability of environmentally friendly thermal insulation based on natural fibre for refrigeration pipe. Here, coconut husk and rice husk are used as the reinforcement and using a mixing ratio of 1:1. Then, fibers are mixed into the flexible foam at a weight percentage anywhere from 5 to 25. The samples are tested in terms of their thermal conductivity. It is observed that the results show acceptable value for the thermal conductivity coefficient, which is between 0.037 and 0.045 Wm−1 K−1. Closer examination found that the conductivity coefficient value is increasing as the fibre content increased. The lowest value of t conductivity coefficient is obtained at 0.037 Wm−1 K−1 for the sample with 5wt and 0.039 Wm−1 K−1 for the sample with 10wt. Thus, these results are within the range of conventional thermal conductivity coefficients.